Iqbal and Bergson on Mystical Experience: A Critique (UCP Journal of Humanities & Social Sciences, 2023)
Iqbal and Bergson have remarkably similar views on Mystical Experience. Both believed in the validity rather superiority of the knowledge achieved through Mystical Experience. Both had a desire to establish knowledge on some firm ground which is beyond any doubt. Moreover, both wished to make room for Metaphysics in an era (20th Century) which was ferociously hostile for this discipline. They had an objective to pave the way for a person in whom individuality has reached its peak and he is able to break the rigid and static world-order to replace it with a dynamic, active, energetic and vibrant one. This paper has used the qualitative methodology and analytical approach to show that Mystical Experience of Both Iqbal and Bergson is not a reliable source of knowledge reliable scientifically, philosophically and even religiously. Major finding of the paper is that mystical experience may not be a valid source of authentic knowledge hence it cannot be taken as the basis of any organized religion. The paper has concluded that it is not a substitute of the Prophetic revelation. Revelation is sent to the select few  of Allah and may never be termed as ‘experience’.